Volunteerism: historical and axiological analysis - Akhmetova, I.A.; Karipbayev, B.I. (KU Publ., 2022)
This article describes the historical and axiological development of volunteerism, which is a modern breakthrough. Today, there are many questions on the emergence of volunteerism, its history and value. During the historical development of volunteerism, the views and works of world philosophers and thinkers are systematized and analyzed on a historical and axiological basis. It is impossible to imagine a society in the history of mankind that is alien to the idea of voluntary and unselfish help. Volunteerism is a quality of human nature that is preserved even in the most difficult times, even in the most difficult years of war and absolutism. The most important thing for voluntariness is the presence of moral values in a person. The scientific significance of the work lies in the study of the development of volunteerism in the philosophical world since ancient times and the basis of research in the views and works of world culture, philosophers and thinkers. The first signs of volunteerism are actions that have taken place through the combined efforts of thousands of people, from traditional aid.
Еріктілік: тарихи-аксиологиялық талдау
Добровольчество: историко-аксиологический анализ
Keywords: volunteerism; axiology; aretology; voluntary work; virtue; charity; humanism; Confucianism; Buddhism